A good death, a bad death, and the mourning between contemporary cocopah - Morales Aguilar, M. Berenice (2025)
The research guiding this article aims to explain how mourning rites are constructed among the Cucapá, dispersed between Baja California and Sonora. It also addresses the Cucapá worldview regarding Good Death and Bad Death, as well as the influence of ritual practices performed by the living to help their deceased reach the other world. The conclusion is that Cucapá cemeteries are not only sacred territories but also fundamental geosymbols that reclaim a small part of the ancestral land that has been taken from them and provide identity to contemporary Cucapá. For the preparation of this article, anthropological research techniques such as direct observation and participant observation were used. Structured and in-depth interviews were also conducted, both in person and via telephone, Zoom, or WhatsApp. Additionally, a review of theoretical and thematic literature on Good Death, Bad Death, and mourning was carried out, as well as on rites of passage and funeral rites, from an anthropological perspective, with the intention of analyzing the presented case study.